2015
DOI: 10.1073/pnas.1503102112
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of a Ni acquisition cycle for [NiFe] hydrogenase by Ni-metallochaperone HypA and its enhancer

Abstract: The Ni atom at the catalytic center of [NiFe] hydrogenases is incorporated by a Ni-metallochaperone, HypA, and a GTPase/ATPase, HypB. We report the crystal structures of the transient complex formed between HypA and ATPase-type HypB (HypB AT ) with Ni ions. Transient association between HypA and HypB AT is controlled by the ATP hydrolysis cycle of HypB AT, which is accelerated by HypA. Only the ATP-bound form of HypB AT can interact with HypA and induces drastic conformational changes of HypA. Consequently, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 42 publications
7
72
0
1
Order By: Relevance
“…HypB is involved in the latter stages of [NiFe]-hydrogenase maturation where it functions together with HypA and the peptidyl-prolyl cis/trans isomerase SlyD to deliver the nickel ion to the active site (Maier et al, 1993;Waugh & Boxer, 1986;Zhang et al, 2005). A recent structural study indicates that HypA proteins likely deliver nickel directly to the hydrogenase large subunit, as exemplified for T. kodakarensis (Watanabe et al, 2015); however, Functional conservation of the Hyp machinery T. kodakarensis lacks a classical HypB protein and instead has a functional homologue (Sasaki et al, 2013) that has an 'enhancer'-like role in facilitating delivery of nickel to the active site by the HypA protein. The data presented here nevertheless suggest that the HypB protein might recognize specific amino acid residues on the apo-large subunits of hydrogenases during maturation, and that D. mccartyi CBDB1 HypB lacks the ability to interact effectively with HyaB, the large subunit of Hyd-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HypB is involved in the latter stages of [NiFe]-hydrogenase maturation where it functions together with HypA and the peptidyl-prolyl cis/trans isomerase SlyD to deliver the nickel ion to the active site (Maier et al, 1993;Waugh & Boxer, 1986;Zhang et al, 2005). A recent structural study indicates that HypA proteins likely deliver nickel directly to the hydrogenase large subunit, as exemplified for T. kodakarensis (Watanabe et al, 2015); however, Functional conservation of the Hyp machinery T. kodakarensis lacks a classical HypB protein and instead has a functional homologue (Sasaki et al, 2013) that has an 'enhancer'-like role in facilitating delivery of nickel to the active site by the HypA protein. The data presented here nevertheless suggest that the HypB protein might recognize specific amino acid residues on the apo-large subunits of hydrogenases during maturation, and that D. mccartyi CBDB1 HypB lacks the ability to interact effectively with HyaB, the large subunit of Hyd-1.…”
Section: Discussionmentioning
confidence: 99%
“…Functional conservation of the Hyp machinery that the limitation in Hyd-1 activity was indeed the HypA metallochaperone-enhancer function provided by HypB (Watanabe et al, 2015). While BEF314 alone failed to synthesize active Hyd-1, even in the presence of 100 mM NiCl 2 , the recovery of Hyd-1 after transformation with pSHH23 confirmed that sufficient levels of functional HypC, D, E and HypF proteins from D. mccartyi were synthesized in the heterologous host to deliver active Hyd-1 (Fig.…”
Section: Mccartyi Hyp E Coli Hyp D Mccartyi Hyp E Coli Hypmentioning
confidence: 99%
“…21 The Ni-sites of the HypA-HypB AT complex show four-coordinate sites with the ligation of the N-terminal amine from Met1, backbone amide and side chain imidazole of His2, and the imidazole side chain from His98. Although this conformation of the Ni-site encompasses both the N-terminal ligation and the four-coordinate planar site, it is unlikely to exist in H. pylori HypA.…”
mentioning
confidence: 99%
“…These results add to the growing body of work that demonstrates that the metal selectivity of metallochaperone activity is not dictated by specific metal binding, but instead is achieved through allosteric coupling, often via partner protein complexes, as observed for example in several studies of the HypA-HypB complex. 2022 …”
Section: Discussionmentioning
confidence: 99%
“…19 One possible strategy, as outlined in several recent reports, is that partner protein interactions modulate selective metal binding and transfer. 2022 …”
Section: Introductionmentioning
confidence: 99%